Optimal design of sandwich panels against quasi-static, impact and blast loading - Lim, Yee Wei (2016)
A sandwich panel has higher bending stiffness and buckling load carrying capacity than a similar weight monolithic panel due to its increased second moment of area. Cellularic materials such as metallic or polymeric foams, lattice structures have better potential in the applications of the core material in sandwich structures over honeycombs and polymer foams due to the cost, durability, anisotropy, creep at ambient temperature and evolution of toxic gases in fires. Among the various metallic foams, aluminium foams such as Alporas™ are widely used due its near isotropic properties, recyclability, good corrosion resistance and light weight. The first research works carried out by the author was to examine the quasi-static indentation responses of the metallic foam cored sandwich panel when subjected to indentation loading in plane strain and axisymmetric loading conditions. The indentation loaded sandwich panels in plane strain condition were experimentally tested and simulated by the finite element analysis. Besides, the indentations loading of sandwich panel in clamped axisymmetric loading condition were investigated by finite element simulation and compared to the limited experimental measurements. There are four competing modes simulated for a given strength ratio of core and face sheets and plate geometry. They are core indentation, core shear, face sheet yielding and face sheet punching. The competing failure modes initial failure loads were taken from the estimates of simply supported plates of Sridhar [5]. By plotting effective von-Mises and shear stress in the core and face sheets for the simulated geometries, the failure modes are clearly identified. It was found that there was a good agreement between the simulation and experimental results which in turn proves that the numerical simulation could be used to predict the failure mode and obtain load-displacement response of the sandwich panel. After the quasi-static study, impact tests on sandwich panels with a fire-resistant polymeric foam core and aluminium face sheet is investigated after thorough mechanical characterisation of constituent materials. The failure modes especially local core indentation is experimentally and numerically probed. The measured load-time responses and indentation damage zone size matched with the numerical simulations well. After the quasi-static and impact studies, another investigation was carried out to study the effectiveness of using polyurethane interlayers in enhancing the performance (energy absorption and deflection) of the Alporas foam cored circular hybrid sandwich structure under an axisymmetric spherical blast loading with fixed boundary condition using ABAQUS finite element software. In the optimization processes, the interlayer and face sheet thicknesses were selected as the design variables within an upper and lower bound constrained by their manufacturing capability. The other designing parameters which might also affect the structure are kept as constant except the dependent variable which is the core thickness was varying due to the variation of design variables and the total height constraint. There are 48 sets of distinctive design configurations generated through modified Latin Hypercube Sampling for finite element simulation to get the numerical output response of the structure. Next, the Kriging metamodel was adopted to estimate the untried finite element results to refine the input for the optimization in order to achieve a much realistic optimization result. Finally, the Kriging metamodel was employed in the development of multi objective optimization process which is capable of flexibly synthesizing a set of good trade-off solutions known as the Pareto-optimal solutions of blast resistance hybrid sandwich structure for any given objectives. Subsequently, blast resistance doors are numerically designed against spherical blast scenario using a combination of rolled homogeneous steel alloy (RHA) steels and square honeycomb filled with polyurethane interlayer. Eight configurations were designed to study the significant effects of interlayer thickness, face sheet thickness, core thickness, cell wall thickness and radius of curvature of the sandwich door. The desired objective of this study is to choose the sandwich panel with minimum deflection on the door panel, maximum energy absorption on the door panel and minimum reaction force on the door frame.